2019
DOI: 10.1111/spc3.12502
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond categorization to understand affective influences on real world health decisions

Abstract: This paper provides an overview of affect and health decision-making research, with a focus on identifying gaps, opportunities, and challenges to guide future research. We begin by defining common categorical distinctions of affective processes that influence health decisions: integral (i.e., related to the decision) and incidental (i.e., normatively unrelated to the decision) influences, and current (experienced in the moment) and anticipated ("cognitive representations" of future affect) affect. We then summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 121 publications
(184 reference statements)
0
12
0
Order By: Relevance
“…As such, we selected a potentially less ecologically valid induction method in favor of experimental control. Future research should, however, seek to replicate and extend to address this limitation by developing and using different induction (and measurement) methods to triangulate knowledge to answer the question of whether integral and incidental emotions influence decisions similarly or differently (see Ferrer & Ellis, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we selected a potentially less ecologically valid induction method in favor of experimental control. Future research should, however, seek to replicate and extend to address this limitation by developing and using different induction (and measurement) methods to triangulate knowledge to answer the question of whether integral and incidental emotions influence decisions similarly or differently (see Ferrer & Ellis, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Given that some of these audiences may believe that COVID-19 risk and severity are exaggerated and consequently become disengaged, communicating the risk of contracting COVID-19 may be an important part of the vaccine education message (Tannenbaum et al, 2015). Neglecting to do so may elicit message avoidance and further de-activate emotions (Janis & Feshbach, 1953;Ness et al, 2017), consequently reducing the perceived need for vaccination. In sum, "one size does not fit all," and we must avoid generic messages and instead consider the emotional states of different audiences in targeted and tailored vaccine communication efforts.…”
Section: Counteracting Negative Emotionsmentioning
confidence: 99%
“…One strategy to leverage positive emotional appeals is framing vaccine messages to appeal to altruism and the positive impacts of vaccination on the wider community ("prosocial motivations") (Jordan et al, 2020;Ojala, 2012). Prosocial message framing has been shown to elicit positive emotions such as hope or joy (Bavel et al, 2020;Lwin et al, 2020;Ojala, 2012), which may counteract some of the collective negative emotions and consequential passivity and message avoidance (Janis & Feshbach, 1953;Morgul et al, 2020;Ness et al, 2017;Seligman, 1975Seligman, , 1981. Additionally, there may be opportunities to appeal to positive emotions by highlighting the importance of family and community connections and the collective desire to return to closer interactions after a prolonged period of social distancing and isolation (World Health Organization, 2020).…”
Section: Activating Positive Emotionsmentioning
confidence: 99%
“…Although medical practice has recognized the importance of emotions in communication training and in teaching HCPs how to manage the emotional burden of their work (Bry et al, 2016;Cricco-Lizza, 2014), incorporating emotions into the decision-making process is less common (Ferrer et al, 2015). In fact, evidence has shown that depending on the circumstances emotions can facilitate or hinder decision-making (Ferrer & Ellis, 2019). In the context of a prenatal diagnosis, some studies have showed that emotions can influence the decision-making process (Gengler, 2020;St-Jacques et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should further investigate the dynamic and influence of emotions on prenatal decisionmaking and incorporate it into clinical practice (Ferrer & Ellis, 2019;Gengler, 2020). In addition, such future work should take into consideration the complexity of such an endeavor.…”
Section: Discussionmentioning
confidence: 99%